2020
DOI: 10.1139/bcb-2019-0256
|View full text |Cite
|
Sign up to set email alerts
|

PLOD2 promotes aerobic glycolysis and cell progression in colorectal cancer by upregulating HK2

Abstract: The purpose of this study was to characterize the expression of procollagen-lysine, 2-oxoglutarate 5-dioxygenase 2 (PLOD2), a membrane-bound homodimeric enzyme that specifically hydroxylates lysine in the telopeptide of procollagens, and assess the clinical significance of PLOD2 in colorectal cancer (CRC). Our results show that PLOD2 is highly expressed in CRC tumor tissues and cell lines, both at the mRNA and protein levels. Next, we found that PLOD2 was positively correlated with tumor grade (P = 0.001), T s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 34 publications
4
23
0
Order By: Relevance
“…Recent studies have reported that STAT3 might play a crucial role in maintaining glycolysis in cancer cells by regulating HK2 (Li et al, 2015;Liu and Yu, 2018). In CRC cells, using STAT3 phosphorylation inhibitor cryptotanshinone could significantly decrease the HK2 expression (Du et al, 2019). Also, siRNAknockdown STAT3 in CRC cells decreased mRNA levels of HK2 by reducing STAT3 recruitment to HK2 promoter (Du et al, 2019), consistent with the findings in breast cancer cells (Jiang et al, 2012).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Recent studies have reported that STAT3 might play a crucial role in maintaining glycolysis in cancer cells by regulating HK2 (Li et al, 2015;Liu and Yu, 2018). In CRC cells, using STAT3 phosphorylation inhibitor cryptotanshinone could significantly decrease the HK2 expression (Du et al, 2019). Also, siRNAknockdown STAT3 in CRC cells decreased mRNA levels of HK2 by reducing STAT3 recruitment to HK2 promoter (Du et al, 2019), consistent with the findings in breast cancer cells (Jiang et al, 2012).…”
Section: Discussionsupporting
confidence: 82%
“…In CRC cells, using STAT3 phosphorylation inhibitor cryptotanshinone could significantly decrease the HK2 expression (Du et al, 2019). Also, siRNAknockdown STAT3 in CRC cells decreased mRNA levels of HK2 by reducing STAT3 recruitment to HK2 promoter (Du et al, 2019), consistent with the findings in breast cancer cells (Jiang et al, 2012). On the basis of these observations, we assessed the importance of STAT3 signaling with regards to the ability of AT-I to mediate anticancer effects in CRC cells.…”
Section: Discussionsupporting
confidence: 67%
“…STAT3 binding to the promoter region of HK2 regulates its expression in transcriptional level. The STAT3 knockdown using lipofectamine 2000 in SW480 cells decreased its recruitment to HK2 promoter and thereby, reduced HK2 expression 113 …”
Section: Signal Transduction Pathwaysmentioning
confidence: 99%
“…More importantly, the knockdown of STAT3 substantially improved the chemosensitivity of LoVo cells to fluorouracil. 112 Du et al 113 investigated the effect of STAT3 silencing on hexokinase 2 (HK2) expression. HK2 enzyme catalyzes the conversion of glucose to 6-phosphate-glucose, the irreversible first stage of glycolysis.…”
mentioning
confidence: 99%
See 1 more Smart Citation